Analysis of Farmers’ Perceptions and The Prospect of Wanamina Ponds Develoment (Silvofishery) in Muara Badak District, Kutai Kartanegara Regency - Fahrony, Abdul Azis; Elly Purnama Sari, Bambang I Gunawan, (Universitas 17 Agustus 1945 Samarinda, 2018)
This study aims to determine the farmers’ perception about wanamina silvofishery, comprehend the feasibility of Wanamina silvofishery and the strategy of developing Wanamina silvofishery in Muara Badak subdistrict.The results of this research are as follows; The farmers’ perception about Wanamina silvofishery is on the average score of 772, signifies high category. This means their perceptions on Wanamina silvofishery are positive and the farmers support wanamina silvofishery as a farming system that can preserve the environment. Meanwhile, farmers’ perception that believe Wanamina silvofishery increases income is 332, signifies moderate category. This means Wanamina silvofishery still cannot increase the farmers’ income. The results of business analysis show the NPV (Net Present Value) of Rp. 17.643.973which signifies feasible. The value of IRR (Internal Rate of Return) is 15% which signifies feasible, and the value of NBCR (Net Benefit Cost Ratio) is 1,5 which signifies feasible. Overall, the Wanamina silvofishery business in Muara Badak subdistrict is feasible to develop. The result of SWOT analysis resulted on the development strategies of Wanamina silvofishery are as follows: (1) develop the economic improvement programs and added value for Wanamina farmers; (2) Strengthen the capacity of the Fisheries Office and the partnerships among stakeholders; (3) Proper management of seeds and mangrove plants in Wanamina silvofishery; (4) Improve the facilities and infrastructure to increase the performance of Wanamina silvofishery; (5) Develop technical manuals in cultivating Wanamina silvofishery; (6) Develop pilot project of wanamina silvofishery as a community pilot; (7) Increase the quality of Fisheries PPL especially in the field of aquaculture; (8) Increase public awareness about Wanamina silvofishery through counseling and socialization.Based on the aforementioned results, the researcher suggests to conduct a more in-depth study of Wanamina silvofishery, organize comprehensive programs that involve all parties; government, private and farmers, and establish a model silvofishery that becomes a reference for farmers as excellent silvofishery management.